2019
DOI: 10.1021/acsami.9b14772
|View full text |Cite
|
Sign up to set email alerts
|

Rubidium Doping to Enhance Carrier Transport in CsPbBr3 Single Crystals for High-Performance X-Ray Detection

Abstract: The direct band gap CsPbBr3 perovskite is regarded as a promising alternative for low-cost and high-performance X-ray radiation detectors. Despite the fact that CsPbBr3 nanocrystals have been shown to be good scintillators in the indirect conversion mode, the direct X-ray conversion with CsPbBr3 single crystals is expected to yield higher spatial resolution. Here, rubidium (Rb) doping is demonstrated to be an efficient approach to improve carrier transport and X-ray detection performance in the direct-conversi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
90
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(91 citation statements)
references
References 44 publications
1
90
0
Order By: Relevance
“…However, the methodology on how to properly determine the detection limit has not been able to catch up with the rapid development of perovskite materials and their applications for X-ray detection. Many publications [12][13][14][16][17][18][19] have only reported the sensitivity of their perovskite X-ray detectors, while lacking the measure of the detection limits (Fig. 1).…”
mentioning
confidence: 99%
“…However, the methodology on how to properly determine the detection limit has not been able to catch up with the rapid development of perovskite materials and their applications for X-ray detection. Many publications [12][13][14][16][17][18][19] have only reported the sensitivity of their perovskite X-ray detectors, while lacking the measure of the detection limits (Fig. 1).…”
mentioning
confidence: 99%
“…From XPS analysis (Figure 2b,c), it is observed that the binding energy difference of Hf4f and Cl2p is increased by 0.16 eV with the incorporation of Sb 3+ . It means that the chemical interaction between the Hf 4+ cations and Cl – anions is somewhat enhanced, [ 20 ] which helps to stabilize the [HfCl 6 ] 2‐ octahedrons through suppressing the diffusion of Hf 4+ or Cl – ions away from [HfCl 6 ] 2‐ octahedrons or the break of the Hf–Cl bond during the NCs’ formation, thereby mitigating Hf 4+ as well as I ‐ vacancy defects of [HfCl 6 ] 2‐ octahedrons. As far as we know, Sb 3+ ‐ assisted passivation has rarely been achieved in the studies of perovskite NCs.…”
Section: Resultsmentioning
confidence: 99%
“…Photoconductivity measurement indicated that the μτ product was increased from 4.9 × 10 −4 cm 2 V −1 for pristine CsPbBr 3 to 7.2 × 10 −4 cm 2 V −1 for RbCsPbBr 3 . As a result, the RbCsPbBr 3 detector delivered a much higher sensitivity of 8097 μC Gy air −1 cm −2 as compare to that of the CsPbBr 3 detector (918 μC Gy air −1 cm −2 ) 80 …”
Section: Materials Engineering Of Perovskite X‐ray Absorbermentioning
confidence: 99%